Pengukuran Kebergunaan dan Pengalaman Pengguna Marketplace Jogjaplaza.id - Vieka Aprilya Intanny; Inasari Widiyastuti; Maria Dolorosa Kusuma Perdani (BBPSDMP KOMINFO MAKASSAR, 2018)
Good usability and user experience are indicators to measure the quality of information system. Among multiple e-marketplace service providers, manager is expected to provide understandable and learnable service and enjoyable user experience. Jogjaplaza.id is an e-marketplace managed by local government for small medium enterprise. The aim of this paper is to measure usability and user experience of small medium enterprise towards Jogjaplaza.id. By using UEQmethod and USE Questionnaire, it could be concluded that Jogjaplaza.id is easy to understand and to learn. Jogjaplaza.id shows positive evaluation for pragmatic and hedonic aspects. However, users perceive lower level of innovation at Jogjaplaza.id. Users assume that the service provided by Jogjaplaza.id is not supporting e-commerce transaction although it is enjoyable and easy to use.